2014
DOI: 10.15244/pjoes/26277
|View full text |Cite
|
Sign up to set email alerts
|

Natural Radioactivity of Solid and Liquid Phases from Shale oil and Gas Prospecting in Pomerania

Abstract: Ionizing radiation intensity data and estimation of equivalent absorbed doses from solid and liquid samples from prospecting shale gas and oil at select sites in Pomerania are presented. Naturally occurring radioactive materials (NORM) are associated with geological formations or fluids and can be enhanced during oil and gas production. They appear in e.g. drilling cuttings, flow-back water, produced water, scale, and sludge. In this study only gamma rays were detected and their intensity was comparable to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Mixing with fly-ash, gypsum may restrain the leaching of those elements [1,25]. Earlier studies have shown that drilling waste do not pose any risk related to radioactivity [26][27][28]. Due to high content of barium sulfate, the waste may be used for preparation cement with high chemical and heat resistance and opaque to X-ray radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Mixing with fly-ash, gypsum may restrain the leaching of those elements [1,25]. Earlier studies have shown that drilling waste do not pose any risk related to radioactivity [26][27][28]. Due to high content of barium sulfate, the waste may be used for preparation cement with high chemical and heat resistance and opaque to X-ray radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring radioactive materials may be enhanced above NORM levels due to a number of human activities such as petroleum explorations, mining, fertilizer production, iron and steel production, extraction of coal, building materials industry and (uranium and thorium) mining etc [4]. Petroleum explorations cause NORM to be accumulated and elevated up NORM levels during drilling and processing of petroleum [5,6,7]. The uncontrolled release of radioactive material due to petroleum exploration may pollute the environment represents potential environmental and health risks to the worker if not properly handled [4].…”
Section: Introductionmentioning
confidence: 99%